Accuracy of digital impression scanning strategies for free-end edentulous - Athirah, Annisa; Haslinda Z. Tamin; Ricca Chairunnisa (Indonesian Journal of Prosthodontic, 2025)
Background: Scanning using intraoral scanners (IOS) offers better accuracy and time efficiency compared to conventional impression methods, especially in overcoming the challenges of free end edentulous cases. The quality of IOS scans is measured by accuracy, which is influenced by scan strategy. Scan strategies include scanning paths, sequences, and combinations. Study conducted that the right scan strategy can affect accuracy as assessed by trueness and precision. However, there is no manufacturer's standard and only a few study on scan strategies in edentulous free end cases. Objectives: This literature review aims to describe scan strategy in improving digital impression accuracy in free end edentulous case. Summary: A zig zag scanning path will help the IOS to capture the tooth morphology better and a linear scanning path will result in smaller deviations. Scanning sequences from the teeth to ridge will reduce the jigsaw effect at the fulcrum point, resulting in a more stable framework during removable denture fabrication. Keywords: Scan strategy; IOS; free end; trueness; precision